FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAUAN MEMBAYAR PAJAK WAJIB PAJAK ORANG PRIBADI YANG MELAKUKAN PEKERJAAN BEBAS (studi empiris pada KPP Pratama Pekanbaru Tampan) - Weni Khastuti; Enni Savitri; Rheny Afriana Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The purpose of this study was to examines the influence paying tax awareness, knowledge and understanding of tax regulation, a good perception of the effectiveness of the taxation system, the quality of tax services on the willingness to pay taxes of an personal taxpayer who performs work free. Sampling techniques in the study was probability sampling. To better represent the researchers took a sample of 78 respondents with Slovin formula calculations. This study uses quantitative methods, where the data obtained from distributing questionnaires to the taxpayer who performs registered in KPP Pratama Tampan, Pekanbaru. Test statistic used is multiple linear regression test, and data obtained were processed using SPSS 20.0. Statistical software. Based on the results of research that conducted, found the coefficient of determination (Adj. R²) of 0.581. That means 58,1% of the willingness to pay taxes influenced by paying tax awareness, knowledge and understanding of tax regulation, a good perception of the effectiveness of the taxation system,the quality of tax services. The independent variable in this study paying tax awareness, knowledge and understanding of tax regulation,the quality of tax serviceshad a significant influence on the willingness to pay taxes. Then independent variable a good perception of the effectiveness of the taxation system doesn't influence on the willingness to pay taxes of an personal taxpayer who performs work free.Keywords: Willingness, awareness, knowledge, perception and quality